Effectiveness of intra-articular lidocaine injection for reduction of anterior shoulder dislocation: randomized clinical trial Efetividade da injeção intrarticular de lidocaína na redução das luxações anteriores do ombro: ensaio clínico randomizado - Marcel Jun Sugawara Tamaoki; Flavio Faloppa; André Wajnsztejn; Nicola Archetti Netto; Marcelo Hide Matsumoto; João Carlos Belloti (São Paulo Medical Journal, 2012)
CONTEXT AND OBJECTIVE: Shoulder dislocation is the most common dislocation among the large joints. The aim here was to compare the effectiveness of reduction of acute anterior shoulder dislocation with or without articular anesthesia. DESIGN AND SETTING: Prospective randomized trial conducted in Escola Paulista de Medicina, Universidade Federal de São Paulo (EPM-Unifesp). METHODS: From March 2008 to December 2009, 42 patients with shoulder dislocation were recruited. Reductions using traction-countertraction for acute anterior shoulder dislocation with and without lidocaine articular anesthesia were compared. As the primary outcome, pain was assessed through application of a visual analogue scale before reduction, and one and five minutes after the reduction maneuver was performed. Complications were also assessed. RESULTS: Forty-two patients were included: 20 in the group without analgesia (control group) and 22 in the group that received intra-articular lidocaine injection. The group that received intra-articular lidocaine had a statistically greater decrease in pain over time than shown by the control group, both in the first minute (respectively: mean 2.1 (0 to 5.0), standard deviation, SD 1.3, versus mean 4.9 (2.0 to 7.0, SD 1.5; P < 0.001) and the fifth minute (respectively: mean 1.0; 0 to 3.0; SD = 1.0 versus mean 4.0; 1.0 to 6.0; SD = 1.4; P < 0.001). There was one failure in the control group. There were no other complications in either group. CONCLUSION: Reduction of anterior shoulder dislocation using intra-articular lidocaine injection is effective, since it is safe and diminishes the pain. CLINICAL TRIAL REGISTRATION: ISRCTN27127703. CONTEXTO E OBJETIVO: A luxação do ombro é a mais frequente luxação das grandes articulações. O objetivo foi comparar a efetividade da redução da luxação anterior aguda do ombro, com ou sem anestesia articular. TIPO DE ESTUDO E LOCAL: Ensaio clínico randomizado desenvolvido na Escola Paulista de Medicina - Universidade Federal de São Paulo (EPM-Unifesp). MÉTODOS: De março de 2008 a dezembro de 2009 foram recrutados 42 pacientes com luxação anterior do ombro agudas. Foi comparada a redução de tração e contra-tração com e sem anestesia intra-articular com lidocaína. Como desfecho primário, a dor foi avaliada por meio da escala visual analógica antes da redução e um e cinco minutos após a redução do ombro. Complicações também foram avaliadas. RESULTADOS: Foram incluídos 42 pacientes: 20 no grupo sem anestesia (grupo controle) e 22 no grupo que recebeu injeção intra-articular de lidocaína. O grupo que recebeu lidocaína intra-articular teve estatisticamente menos dor no primeiro (média = 2,1; 0 a 5,0, desvio padrão, DP, de 1,3, versus média = 4,9; 2,0 a 7,0; DP = 1,5; respectivamente; P < 0,001) e no quinto minutos (média = 1,0; 0 a 3,0; DP = 1,0 versus 4,0; 1,0 a 6,0; DP = 1,4; respectivamente; P < 0,001) após a redução em comparação ao grupo controle. Houve uma falha no grupo controle. Não houve complicações adicionais em ambos os grupos. CONCLUSÃO: A redução da luxação do ombro com o uso de lidocaína intra-articular é efetiva, pois é segura e proporciona menos dor. REGISTRO DE ENSAIO CLÍNICO: ISRCTN27127703